2008
DOI: 10.2527/jas.2007-0603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Bacillus-based direct-fed microbial feed supplement on growth performance and pen cleaning characteristics of growing-finishing pigs

Abstract: A direct-fed microbial (DFM) based on a combination of Bacillus organisms specifically selected to increase the manure decomposition process was evaluated to determine its efficacy for improving growth performance and manure dissolution time. Three experiments involving 336 crossbred barrows and gilts were conducted to determine the effect of the Bacillus-based direct-fed microbial on growth performance and pen cleaning time. In each experiment, 2 dietary treatments (0 and 0.05% DFM) were fed during the growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 14 publications
5
98
1
2
Order By: Relevance
“…A clear dose-effect was observed in the reduction of organic matter from 17% to 41% in mass terms (11% to 32% in COD units), when the additive was supplemented at 250 mg/kg (T2) and 500 mg/kg (T3), respectively. These results are in agreement with a previous study, in which dietary supplementation with a combination of B. lichenformis and B. subtilis strains improved feed efficiency in growing pigs and decreased the swine manure viscosity and content of solids (Davis et al, 2008). Here, the most important reduction in pig slurry organic matter concerns proteins, from 20% in T2 to 46% in T3, either in mass and COD units, when compared with the control T1 (Table 2).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A clear dose-effect was observed in the reduction of organic matter from 17% to 41% in mass terms (11% to 32% in COD units), when the additive was supplemented at 250 mg/kg (T2) and 500 mg/kg (T3), respectively. These results are in agreement with a previous study, in which dietary supplementation with a combination of B. lichenformis and B. subtilis strains improved feed efficiency in growing pigs and decreased the swine manure viscosity and content of solids (Davis et al, 2008). Here, the most important reduction in pig slurry organic matter concerns proteins, from 20% in T2 to 46% in T3, either in mass and COD units, when compared with the control T1 (Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…There are growing numbers of reports which document survival and germination of Bacillus spores within the digestive tract (Nicholson, 2002). Due to enhanced enzyme contact, less incidence of foaming and lower accumulation of solids, fibre-bound nitrogen, total protein and fats are expected in the manure pit (Davis et al, 2008). Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Species within Bacillaceae have also been shown to improve animal health. For example, Bacillus subtilis as a direct fed microbial has been shown to increase weight gain and feed conversion rates in broiler chickens (Molnar et al, 2011), improve average daily gain while reducing the mortalities of pigs during the growing-finishing period (Davis et al, 2008), and enhance immune function in calves (Sun et al, 2010) and broiler chickens Molnár et al (2011). Certain Bacillus spp.…”
Section: Histophilus Somni Mannheimia Haemolytica Pasteurella Multocidamentioning
confidence: 98%
“…Puphan et al [48] reported a reduction in fecal ammonia and hydrogen sulfide, both highly noxious gases, from swine that were supplemented orally with a combination of B. subtilis and B. amyloliquefaciens. Furthermore, when a combination of B. subtilis and Bacillus licheniformis was administered to growing pigs, manure from the pens dispersed more quickly, meaning that pens could be cleaned and manure solubilized more quickly for a less noxious waste product [60]. These data indicate that a positive impact on humans that goes far beyond the direct health/non-health dichotomy can be mediated by probiotics.…”
Section: Swinementioning
confidence: 73%